Short Communication: Single nucleotide polymorphism in C-type lysozyme gene and its correlation with Aeromonas hydrophila resistance in African catfish Clarias gariepinus - Hasan Nasrullah; Yanti Inneke Nababan; Ika Safitri; Dwi Yanti; Sri Nuryati; Muhammad Zairin Jr; Alimuddin Alimuddin (Society for Indonesian Biodiversity, 2020)
Abstract. Authors. 2020. Short Communication: Single nucleotide polymorphism in C-type lysozyme gene and its correlation with Aeromonas hydrophila resistance in African catfish Clarias gariepinus. Biodiversitas 21: 311-317. The chicken-type lysozyme (LYSC) gene has been demonstrated to play important roles in the fish protection system against bacterial infection. In this present study, we aimed to identify the single nucleotide polymorphism (SNP) within the LYSC gene of African catfish Clarias gariepinus and its possible association with Aeromonas hydrophila resistance, a major pathogenic bacterium in African catfish. The gDNA of the African catfish LYSC coding sequence was 1559 bp long, comprising of four exons and three introns. Six SNPs were identified in African catfish LYSC, namely SNP1-6. After the A. hydrophila challenge, we regarded the surviving individuals after the infection as the resistant group and the dead fish as the susceptible group. High-resolution melting (HRM) analysis on SNP2 revealed that the allele frequencies of TT, CC, and TC were of 27.78%, 5.55%, and 66.67% in the resistant group, while the frequencies of TT, CC, and TC were 16.67%, 27.78%, and 55.55% in the susceptible group, respectively. The expression of LYSC and other immune-genes in the resistant group was also higher in the liver, head kidney, and spleen. These results indicated that the LYSC gene might play an essential role in bacterial resistance, and the SNP2 within the LYSC gene may be associated with the resistance to A. hydrophila in African catfish.